Landasan Teori Konseling Islam - Mukhlas Mukhlas; Ika Kurnia Sofiani (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2021)
This article aims to understand the basic concepts of counseling in Islam which are derived from the Qur'an and Hadith. Data related to counseling were analyzed using the content analysis technique and then interpreted using a qualitative descriptive approach. The findings and conclusions in this article are that Islamic counseling is an activity of providing advice, guidance, and lessons to individuals in need based on the foundation of Islamic teachings, namely al-Qur'an and al-Sunnah. Based on the al-Quran, Islamic counseling must contain at least three main concepts, namely al-hikmah, al-mauidhah al-hasanah, and al-muajadalah bi al-ihsan. Meanwhile, based on the hadith, the implementation of Islamic counseling puts forward the concept of counseling where the counselor must be a role model or uswatun hasanah. Islamic counseling must also elaborate Philosophical, Psychological, Theological, Sufistic, Socio-Cultural, and Pedagogical foundations.Artikel ini bertujuan untuk memahami konsep dasar konseling dalam Islam yang bersumber dari al-Qur’an dan Hadis. Data-data terkait konseling dianalisa menggunakan teknik content analysis dan kemudian diinterpretasikan dengan pendekatan deskriptif kualitatif. Temuan dan simpulan dalam artikel ini adalah, konseling Islam merupakan aktivitas pemberian nasihat, bimbingan, pelajaran kepada individu yang membutuhkan yang aplikasinya didasarkan pada landasan ajara Islam, yaitu al-Qur’an dan al-Sunnah. Berdasarkan al-Qur’an, konseling Islam setidaknya harus memuat tiga konsep utama yaitu al-hikmah, al-mauidhah al-hasanah, dan al-muajadalah bi al-ihsan. Sementara berdasarkan hadits, pelaksanaan konseling Islam mengedepankan konsep nasihat-menasihati dimana konselor harus menjadi teladan atau uswatun hasanah. Konseling Islam juga harus dielaborasi dengan landasan filosofis, psikologis, teologis, sufistik, sosial budaya, dan landasan pedagogis.